2015
DOI: 10.5152/tpd.2015.3761
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Cutaneous Leishmaniasis with Amphotericin B; A Case of Unresponsive to Pentavalent Antimony Therapy

Abstract: Cutaneous Leishmaniasis (CL) is a skin infection caused by various species of Leishmania parasites, which is transmitted by infected Phlebotomus sandfly bites. Pentavalent antimonials (meglumine antimoniate and sodium stibogluconate) are used for the treatment of adult CL patients as an effective and safe method. Liposomal amphotericin B is an alternative for the treatment of choice in cutaneous leishmaniasis cases which pentavalan antimony contraindicated or unresponsive to pentavalent antimony therapy. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 1 publication
0
4
0
2
Order By: Relevance
“…Nanosilver damage DNA, denature proteins and enzymes and produce free radicals and some studies showed that nanosilver is cytotoxic to several different cell lines [1,38]. The teratogenicity of nanosilver in humans is indistinctive and is not reported in the literature but in vivo (animal studies) and in vitro studies showed nanosilver can exhibit a significant level of toxicity [39]. Nano-mediated drug delivery of plant-derived products is one of the most important strategies for the treatment of visceral leishmaniasis (VL) in the absence of adequate anti-leishmanial drugs.…”
Section: Application Of Nano Drugs In Treatment Of Leishmaniasismentioning
confidence: 99%
See 1 more Smart Citation
“…Nanosilver damage DNA, denature proteins and enzymes and produce free radicals and some studies showed that nanosilver is cytotoxic to several different cell lines [1,38]. The teratogenicity of nanosilver in humans is indistinctive and is not reported in the literature but in vivo (animal studies) and in vitro studies showed nanosilver can exhibit a significant level of toxicity [39]. Nano-mediated drug delivery of plant-derived products is one of the most important strategies for the treatment of visceral leishmaniasis (VL) in the absence of adequate anti-leishmanial drugs.…”
Section: Application Of Nano Drugs In Treatment Of Leishmaniasismentioning
confidence: 99%
“…Nano-mediated drug delivery of plant-derived products is one of the most important strategies for the treatment of visceral leishmaniasis (VL) in the absence of adequate anti-leishmanial drugs. Artemisinin has been traditionally used for the treatment of malaria and has been reported to exhibit anti leishmanial and antitumor activities [2,[38][39][40]. Earlier, it has been proved that formulation of artemisinin-loaded nanoparticles improved its activity against L. donovani amastigotes ex vivo [17].…”
Section: Application Of Nano Drugs In Treatment Of Leishmaniasismentioning
confidence: 99%
“…DSÖ'ne göre her yıl çoğu gelişmekte olan ülkelerden yaklaşık 2 milyon yeni vaka bildirilmekte olup12 milyon insanı etkilemektedir [10] . Leishmaniasis tedavisinde beş değerli antimon bileşik-leri, amfoterisin B deoksikolat, miltefosin, paromomisin, sitamaquin, azoller ve pentamidin gibi farklı anti-leishmanial ajanların yanında termoterapi ve kriyoterapi gibi uygulamalar da kullanılmaktadır [19][20][21] .…”
Section: Tartişma Ve Sonuçunclassified
“…Tedavisinde kullanılan beş değerli antimon bileşiklerinin etkinliğinin %90'ın üzerinde olduğu bildirilirken, miyalji, artralji, karın ağrısı, hepatit, pankreatit ve çeşitli laboratuvar değerlerinde yükseklik gibi nadiren lokal ve sistemik yan etkilere neden olabileceği de rapor edilmiştir [21] . Amfoterisin B ise vücutta geniş bir yayılım göstermesi nedeniyle, infüzyon reaksiyonları, nefrotoksisite, hipokalemi ve miyokardit gibi yan etkilere sahiptir ve hasta 4-5 hafta yatarak takip edilmektedir.…”
Section: Tartişma Ve Sonuçunclassified
“…The underlying barricades towards their failure were high toxicity, delayed drug release and response; inimical side effects and development of resistance towards the available drug regimen [5] [6]. One of the contemporary approaches includes the use of amphotericin B accompanied by emanation of miltefosine as the first oral drug therapy for VL [7]. In the conquest for identifying better leishmanicidal compounds, plant-derived and/or mimicking products have been gaining ground.…”
Section: Introductionmentioning
confidence: 99%